Smart Hedging Against Carbon Leakage - Christoph Böhringer; Knut Einar Rosendahl; Halvor Briseid Storrøsten (Center for Economic Studies and ifo Institute (CESifo), 2019)
Policy makers in the EU and elsewhere are concerned that unilateral carbon pricing induces carbon leakage through relocation of emission-intensive and trade-exposed industries to other regions. A common measure to mitigate such leakage is to combine an emission trading system (ETS) with output-based allocation (OBA) of allowances to exposed industries. We first show analytically that in a situation with an ETS combined with OBA, it is optimal to impose a consumption tax on the goods that are entitled to OBA, where the tax is equivalent in value to the OBA-rate. Then, using a multi-region, multi-sector computable general equilibrium (CGE) model calibrated to empirical data, we quantify the welfare gains for the EU to impose such a consumption tax on top of its existing ETS with OBA. We run Monte Carlo simulations to account for uncertain leakage exposure of goods entitled to OBA. The consumption tax increases welfare whether the goods are highly exposed to leakage or not, and can hence be regarded as smart hedging against carbon leakage.
Keywords: D61; F18; H23; Q54; 330; carbon leakage; output-based allocation; consumption tax